Keterampilan Berpikir Kritis Siswa Melalui Penerapan Model Discovery Learning Pada Materi Alat Optik - Shoddiq Shoddiq; Nurul Septiana; Nur Inayah Syar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The research background is an implementation of Limited Face-to-Face Learning because there is COVID-19 that was implemented at MTs Muslimat NU Palangka Raya, and still didn’t know students’ critical thinking skills with discovery learning model implementation on the optical tool's material. The Discovery learning is able to provide learning using a combination of class and home that can be applied according to learning conditions or at a certain time. This learning can also provide competence to students through several learning syntaxes in it. So that this combined learning can determine students' critical thinking skills through their application. The research objective is to describe the students’ critical thinking skills with discovery learning model implementation on the optical tool's material. This research used a descriptive qualitative approach. Subjects in this research were fourteen students of VIII A class. Data analysis techniques used students’ critical thinking skill tests. The data obtained were analyzed descriptively. The results showed that the implementation of discovery learning model on optical tools material through discovery learning syntax was still not implemented well because learning system in the school was Limited Face-to-Face Learning and students’ critical thinking skills by using discovery learning model on optical tools material was quite critical this thing caused by the learning system in the school was Limited Face-to-Face Learning. There is one student with moderately critical categories and 11 students with quite critical categories.